Influência de ligantes, força iônica e pH sobre o potencial redox da proteína DevS do Mycobacterium tuberculosis - Barreto, Giamwemberg de Almeida (2018)
Heme-based sensors are a family of proteins that has caught great interest of the scientific community due to their role in several important biological processes. Mycobacterium tuberculosis (Mtb) is the pathogen responsible for causing tuberculosis, currently found in one quarter of the world population in its latent form. This bacterium presents some heme-based sensor proteins including the protein DevS which, together with its response regulator (DevR), are responsible for the entrance of this bacterium into a persistent state of non-replication, known as latency, which is difficult to eliminate. Currently, there is a conflict in the literature regarding the physiological function of the hemeprotein DevS, being suggested by certain groups to work as an oxygen sensor while others indicated as a redox sensor. Here, we present the results of heterologous expression and purification of Mycobacterium tuberculosis DevS protein along with the measurements of the redox potential, Em, at different conditions, such as absence and presence of ligands (CN-, imidazole, CO and NO), different salt concentrations (100, 200 and 500 mmol L-1 NaCl), and pH (6 to 10). The calculated redox potentials were of +11, +96, +392, -147 and -327 mV vs Standard Hydrogen Electrode (SHE) for DevS in the absence of ligands, and bound to CO, NO, imidazole and CN-, respectively. In addition to that, it was estimated the range of redox potential for DevS bound to O2, from +10 to +195 mV. Nonetheless, dissociation constants (Kd) for the imidazole bound to DevS were also calculated by chemical titration, where Kd = 112 x 10-3 and 300 x 10-6 were found for the reduced and oxidized forms of the protein, respectively. Our results indicated that the redox potential of DevS redox potentials are increasingly positive as the ligand strength is intensified, as predicted by the Ligand Field Theory. Furthermore, the redox potential for unbound DevS was shown to be significantly higher than those estimated for Mycobacterium tuberculosis cytosol being consistent, therefore, with the assignment of oxygen sensor function and discarding, thermodynamically, the role as a redox sensor.